2021
DOI: 10.1021/acs.jpcc.1c04980
|View full text |Cite
|
Sign up to set email alerts
|

Pd4O3 Subsurface Oxide on Pd(111) Formed during Oxygen Adsorption-Induced Surface Reconstruction and Its Activity toward Formate Oxidation Reactions

Abstract: Surface reconstruction and surface oxide formation on Pd(111) facet are investigated using density functional theory calculations coupled with particle swarm optimization (PSO) algorithms, and a series of surface oxides and isomers are obtained and evaluated for the catalytic activity toward formate oxidation reactions for the first time. A globally stable Pd 4 O 3 subsurface oxide is identified on Pd(111) facet during the oxygen adsorbedinduced surface reconstruction and featured by three subsurface oxygen at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 74 publications
(118 reference statements)
0
18
0
Order By: Relevance
“…Taking the AgPd–Ag 2 O interface as an example, Fig. 7(c) shows the schematic diagram of the FOR process, and it has been demonstrated that the FOR on Pd-based catalysts in alkaline medium will not generate the poisoning CO* intermediate, so the reaction pathway is considered to occur through the pathway of HCOO − , HCOO − bi *, HCOO − mo *, CO 2 * + H* and CO 2 + H. 6,54…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Taking the AgPd–Ag 2 O interface as an example, Fig. 7(c) shows the schematic diagram of the FOR process, and it has been demonstrated that the FOR on Pd-based catalysts in alkaline medium will not generate the poisoning CO* intermediate, so the reaction pathway is considered to occur through the pathway of HCOO − , HCOO − bi *, HCOO − mo *, CO 2 * + H* and CO 2 + H. 6,54…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] Unfortunately, the development of DFFCs suffers from the bottleneck of poor kinetics for the anodic formate oxidation reaction (FOR). 6 Designing and preparing a FOR catalyst with high catalytic performance and low price is crucial for the wide application of DFFCs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations